Pediatric Chronic Orofacial Pain: A Narrative Review of Biopsychosocial Associations and Treatment Approaches - Sangalli, Linda; Gibler, Robert; Boggero, Ian (Frontiers in Pain Research, 2021)
Pediatric orofacial pain (OFP) is an umbrella term which refers to pain associated with hard and soft tissues of the head, face, and neck in patients younger than 18 years of age (1). The most common chronic pediatric OFP complaints include temporomandibular disorder (TMD), headaches, and neuropathic pain (NP) (2). Pain is classified as chronic when it occurs more than 15 days per month, for at least 3 months, and lasts longer than 4 hours daily (when present) (3). Compared to adults, youth with chronic OFP may have difficulties in verbalizing symptoms (4), may be poor historians, may experience symptoms that are different from those experienced by adults (5), and may not seek treatment as early or as often (4). Parents and other caregivers play important roles in shaping children’s pain experience, and pain in youth affects well-being and functioning in multiple domains. The aims of this mini-review are to describe each of these common chronic pediatric OFP conditions, discuss the roles of psychological, familial and social factors pertinent to conceptualizing the experiences of youth with OFP, and provide a brief overview of evidence-based treatment approaches for children and adolescents with chronic OFP conditions.